Design of the Deadbeat Controller with Limited Output - Balasevicius, L.; Dervinis, G. (Elektronika ir Elektrotechnika, 2011)
There is presented a method for finding the parameters of the deadbeat controller in Matlab environment. The method is based on the introduction of an additional polynomial into the transfer function of the controller. The method for determining the additional polynomial coefficient of a deadbeat controller is based on creating the family of the coefficient curves and defining the permissible selection area. The method was tested by using simulations in Matlab environment and realizing the deadbeat control system for the third order object in the PLC. Simulation results in Matlab show that even though the control increases by one-step, the settling time of the system response can be lower than that of the deadbeat controller without any modifications. Based on the obtained results it can be concluded that the results confirm the idea of defining the parameters of the transfer function of a deadbeat controller with a limited output. Ill. 9, bibl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.296